2017
DOI: 10.1371/journal.pone.0175011
|View full text |Cite
|
Sign up to set email alerts
|

A socioeconomic related 'digital divide' exists in how, not if, young people use computers

Abstract: Government initiatives have tried to ensure uniform computer access for young people; however a divide related to socioeconomic status (SES) may still exist in the nature of information technology (IT) use. This study aimed to investigate this relationship in 1,351 Western Australian children between 6 and 17 years of age. All participants had computer access at school and 98.9% at home. Neighbourhood SES was related to computer use, IT activities, playing musical instruments, and participating in vigorous phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 32 publications
(47 reference statements)
0
58
0
Order By: Relevance
“…LGBTQ youth may turn to social media for important sources of social support (Ybarra et al, 2015). Youth from lower-SES backgrounds may have less consistent access to internet and devices for screen time (Harris et al, 2017), and may engage differently online compared to their higher-SES peers (Micheli, 2016).…”
Section: Media Usementioning
confidence: 99%
“…LGBTQ youth may turn to social media for important sources of social support (Ybarra et al, 2015). Youth from lower-SES backgrounds may have less consistent access to internet and devices for screen time (Harris et al, 2017), and may engage differently online compared to their higher-SES peers (Micheli, 2016).…”
Section: Media Usementioning
confidence: 99%
“…The current sample is not a representative sample and represented a higher socioeconomic status overall. Previous research suggests that the amount of technology use is similar across sociodemographic backgrounds, however the purpose and quality of use may differ (Harris et al 2017 ). Large, representative samples that capture weekly duration, frequency, and purpose of use by device are needed to understand technology use across populations and identify groups who may be in most need of education and intervention to improve the quantity and quality of technology use to achieve better outcomes for children.…”
Section: Discussionmentioning
confidence: 99%
“…The Technology Use Questionnaire (TechU-Q) was developed utilizing 20 years of experience collecting parent and child reports of technology use (Harris and Straker 2000;Harris et al 2017) and existing published surveys of child technology use (Hinkley et al 2012;Houghton et al 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcomes of the research indicated that young people are using more technological tools like mobiles, handheld devices, etc. it may affect the economy, academia and health [27]. In a report presented by OECD for exploring the existence of digital divide, government officials identified that electronic commerce can be improved by increasing the technological use [28].…”
Section: Socio Economics Digital Dividementioning
confidence: 99%